Influence of silica gel dispersion and superplasticizer on the properties of cement paste (Международный научный журнал «Инженер», 2026)
The influence of the dispersion and content of ground silica gel on the properties of cement paste in the presence of a polycarboxylate-based superplasticizer was investigated. Silica gel was introduced in amounts of 5, 10, and 15% by mass of cement, while the superplasticizer dosage was 1%. It was established that an increase in the fineness of silica gel promotes the intensification of hydration processes and the formation of a denser cement paste structure. It was shown that the optimal silica gel content is 5%, at which the maximum strengthening effect is achieved. The incorporation of the superplasticizer reduces the water-to-cement ratio and enhances the compressive strength of the cement paste; however, it is accompanied by an increase in setting time. The highest strength was obtained for the composition containing 5% finely dispersed silica gel and 1% superplasticizer. The observed effect is attributed to the combined action of the additives and the densification of the cement paste structure.